50th anniversary of the department of traumatology, ORTHOPAEDICS AND EXTREME SURGERY N.A. RAS ACADEMICIAN KRASNOV AF - YuV V Lartcev; AP P Chernov; AK K Povelikhin (Наука и инновации в медицине, 2017)
The article presents a report about the work that has been done by the Department of Traumatology, Orthopaedics and Extreme Surgery named after the Academician of the Russian Academy of Sciences Krasnov AF for the years of its existence, and also about the plans for the further development. The stages of formation and development of the department are described. Present state of educational, medical and scientific activities of the team is presented. The article shows what we have achieved during this period. The emphasis is placed on scientific and innovative work, experimental scientific research, and publications.